2012
DOI: 10.1021/cg201677s
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear Complexes Containing Ditopic Bispyrazolylmethane Ligands. Influence of Metal Geometry and Supramolecular Interactions

Abstract: The new ligands bis(pyrazol-1-yl)(pyridine-4yl)methane (bpzm4py) (L1) and bis(3,5-dimethylpyrazol-1yl)(pyridine-4-yl)methane (bpz*m4py) (L2) were synthesized and were made to react with different metallic starting materials. In the case of Pd(II), chloride or allyl trinuclear complexes were synthesized, in which the central palladium is bonded to two ligands through the pyridine moiety. Mononuclear [Pd(allyl)L]X complexes were also isolated. On using other M(II) centers (M = Co, Ni, Zn), which could adopt an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 130 publications
10
50
1
Order By: Relevance
“…However, in this case the region of the metal centre is flatter, and the NMN/N4(pz) angle (163.92°) is larger than that in the square‐planar complexes; this indicates possible steric hindrance between the bidentate nitrate anion and the biphenyl fragment. Coincidentally, larger values for this angle have been found, for example, in octahedral derivatives 23a. In 12 , with this disposition, the aforementioned anion–π interaction is established with an appropriate distance (Figure 8).…”
Section: Resultsmentioning
confidence: 85%
“…However, in this case the region of the metal centre is flatter, and the NMN/N4(pz) angle (163.92°) is larger than that in the square‐planar complexes; this indicates possible steric hindrance between the bidentate nitrate anion and the biphenyl fragment. Coincidentally, larger values for this angle have been found, for example, in octahedral derivatives 23a. In 12 , with this disposition, the aforementioned anion–π interaction is established with an appropriate distance (Figure 8).…”
Section: Resultsmentioning
confidence: 85%
“…Ligand design has became a major concept in these investigations to tailor the stability and chemical properties of the complex [12]. Pyrazole and its derivatives are a crucial member of N-heterocyclic ligands, widely used in coordination chemistry due to their multiple nitrogens taking part in coordination with metals [13][14][15]. Pyrazole and its derivatives have high biological activities and widespread applications in pesticides and medicinal preparations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the final structure depended on the metal geometry and the final products were either discrete species of different nuclearity or polymers. Trinuclear species were formed on employing square‐planar Pd II ions 21. The use of metal centres that were able to give an octahedral geometry, such as Co II , Ni II and Zn II , led, in all cases, to the formation of box‐like cyclic dimers21 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Trinuclear species were formed on employing square‐planar Pd II ions 21. The use of metal centres that were able to give an octahedral geometry, such as Co II , Ni II and Zn II , led, in all cases, to the formation of box‐like cyclic dimers21 (Scheme ). Reaction of the ligands with silver(I) ions provided box‐like cyclic dimers and zig‐zag and helical polymers, with factors such as the coordinating ability of the anions and the crystallisation conditions affecting the structure obtained 22,23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation